Pendidikan Lingkungan Hidup dalam Perspektif Islam - Muhaimin Muhaimin (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2020)
Abstract: Preparing young poeple to be able to solve various environmental problems urgently to be done in order to improve and establish better environmental morality. Islam can be the basic and the main of how to build the character of students towards the environment through environmental education that is integrated with Islamic values. Islam forbids explicitly and harshly for humans to do damage on earth as a source of natural disasters as well as encouraging humans to have good character towards nature. Allah made human as caliph on earth, but in utilizing nature must maintain the balance and preservation of the environment, people who damage the environment are hypocrites and very disliked by Allah. Acording to God that peopole who damage the environment is the very transgressors. Element of Islamic values ​​on the environment can be used as material and the main foundation in environmental education in schools.